Segmenting Revelation in Late Antiquity: Andrew of Caesarea’s Chapter System as a Textual-Canonical Revolution - Mindiola, Cristian Cardozo (Vigiliae Christianae, 2025)
In antiquity, Greek manuscripts underwent a shift toward segmented, non-linear reading, with chapter systems becoming a popular tool. While most New Testament texts quickly adopted chapter systems, Revelation was an exception, reflecting its ambiguous canonical status. This article argues that frequent use of a text, which necessitates segmentation, correlates with its canonicity due to its role in liturgy and pedagogical settings. Revelation’s lack of a chapter system materially signaled its non-canonical perception, as it appeared different from other New Testament texts. In the seventh century CE, Andrew of Caesarea addressed this issue by dividing Revelation into 24 logoi and 72 kephalaia. This segmentation technology not only facilitated its pedagogical use but also made Revelation visually and materially resemble canonical New Testament texts, reinforcing its place in the canon. Thus, Andrew’s chapter system was more than a mundane attempt to divide the text, it was a textual - canonical revolution.